Sistem Pendukung Keputusan Pemilihan Tempat Kegiatan Olahraga di Medan dengan Metode Distance To The Ideal Alternative (DIA) - Raihansyah; Yuyun Dwi Lestari; Yessi Fitri Annisa Lubis (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2022)
Exercise can provide a million benefits for your body. Not only for health, sports activities can also maintain fitness in carrying out daily activities in the midst of a pandemic (currently it is heading towards endemic). The advancement of the times and technology has made it easier for humans to exercise. Exercise can be done in various ways, either using tools or without using tools. Starting from expensive to no costs. Decision support system for the selection of sports venue activities in supporting users with assessments through a system that will be developed using PHP and MySQL programming languages as a database. The program was designed using the DIA method and designed the design using Flowchart, and UML. With the existence of a decision-making support system to make it easier for users to get the best sports venue according to their needs.